2022
DOI: 10.3390/ma15010392
|View full text |Cite
|
Sign up to set email alerts
|

Copper Surface Treatment Method with Antibacterial Performance Using “Super-Spread Wetting” Properties

Abstract: In this work, a copper coating is developed on a carbon steel substrate by exploiting the superwetting properties of liquid copper. We characterize the surface morphology, chemical composition, roughness, wettability, ability to release a copper ion from surfaces, and antibacterial efficacy (against Escherichia coli and Staphylococcus aureus). The coating shows a dense microstructure and good adhesion, with thicknesses of approximately 20–40 µm. X-ray diffraction (XRD) analysis reveals that the coated surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The Cu 2+ release profile exhibited an initial burst release within the first one day (27.33 ± 7.02 ppb), however, it was followed a sustained release over 14 days (up to 40.93 ± 7.88 ppb) ( Fig. S3 ), according to the literature that when the Cu 2+ reached over 36 ppb, the antibacterial efficiency could be more than 99% to both E.coli and S.aureus [ 39 , 40 ]. These results demonstrated that we had prepared the robust antibacterial bio-patches with long-lasting antibacterial performances.…”
Section: Resultsmentioning
confidence: 56%
“…The Cu 2+ release profile exhibited an initial burst release within the first one day (27.33 ± 7.02 ppb), however, it was followed a sustained release over 14 days (up to 40.93 ± 7.88 ppb) ( Fig. S3 ), according to the literature that when the Cu 2+ reached over 36 ppb, the antibacterial efficiency could be more than 99% to both E.coli and S.aureus [ 39 , 40 ]. These results demonstrated that we had prepared the robust antibacterial bio-patches with long-lasting antibacterial performances.…”
Section: Resultsmentioning
confidence: 56%
“…The antibacterial properties of copper are not new and have been widely studied and confirmed by various researchers [ 11 , 26 , 27 , 43 , 44 , 45 , 46 ]. The main objective of this work, however, was to determine whether copper can retain its bactericidal potency for a prolonged period of time under actual operational conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported the virucidal activity of copper against several viruses such as Sars‐CoV‐2, influenza, norovirus, human immunodeficiency virus (HIV), bronchitis virus, and poliovirus, 10,14–16 However, the copper action mechanism is not well described yet; it is reported that copper virucidal action is due to the Cu 1+ and Cu 2+ ions' dissociation from copper compounds. They can cause oxidative stress by reactive oxygen species (ROS) and damage the viral lipid membranes and nucleic acids, leading to virus inactivation 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, the authors observed a rapid Cu 2+ release in aqueous media from nanofibers fabricated, similar to that reported by Phan et al, indicating that Cu 2+ cations action was crucial for the mechanism of action against the bacteria. 11 Recent studies have reported the virucidal activity of copper against several viruses such as Sars-CoV-2, influenza, norovirus, human immunodeficiency virus (HIV), bronchitis virus, and poliovirus, 10,[14][15][16] However, the copper action mechanism is not well described yet; it is reported that copper virucidal action is due to the Cu 1+ and Cu 2+ ions' dissociation from copper compounds. They can cause oxidative stress by reactive oxygen species (ROS) and damage the viral lipid membranes and nucleic acids, leading to virus inactivation.…”
mentioning
confidence: 99%